The Civil Guard: Legislation on the Auxiliary Police - Kardos, Pál (Magyar Rendészet, 2025)
In the field of public security activities, volunteers play a significant role, of which we can see many examples both domestically and abroad. In our country, the civil police is the organisation that has the legal authority to carry out social crime prevention activities as an element of complementary policing. The author of the study undertakes to present, as a practicing law enforcement professional and civil police leader – after a brief look at the establishment of the movement and its reasons – the most important previous and currently running priority programs of the civil police, their reasons, implementation and significance. The author wishes to contribute to the comprehensive scientific research and mapping of the operation of the civil police, recognising the fact that the researched topic of crime prevention, civil participation in maintaining public order and public safety is a timely issue, that under the current circumstances, the role of civil police is an indispensable aid to the police, and that the priority programs contribute to the high-quality performance of civil police tasks, thereby improving the subjective sense of security of citizens. A necessary element of research conducted on this topic is the discussion of the above questions.